BAGAIMANA MENGENALI USAHA MIKRO AGAR BERKELANJUTAN PADA UMKM BINAAN PERMODALAN NASIONAL MADANI JAKARTA BARAT - Nurhayati, Mafizatun; Elmi, Farida; Wilestari, Median (Jurnal Pemberdayaan Masyarakat dan Inovasi, 2024)
Micro, Small and Medium Enterprises (MSMEs) have a strategic role in national economic development. MSMEs play a role in economic growth and labor absorption. MSMEs face many problems that must be faced in running their businesses. In order to be able to play a role in fostering Micro, Small and Medium Enterprises (MSMEs), this time the community service is in collaboration with PT Permodalan Nasional Madani (Persero), a state-owned enterprise that diversifies its funding sources through cooperation with third parties, namely banking and capital markets. In 2015, PT Permodalan Nasional Madani (Persero) launched the PNM Mekaar (Fostering a Prosperous Family Economy) product which provides special services for underprivileged women ultra-micro business actors, both those who want to start a business and develop a business. Our PkM group has the opportunity to become a partner of PT PNM in providing guidance to micro business groups. The implementation is in fostered micro businesses located in Kebagusan Village, West Jakarta. The problem that often occurs which is a characteristic of MSMEs, many MSME business people prefer to change businesses before their business is established and stable, even though by changing businesses frequently, this MSME business will not be able to develop because of such a passionate desire and the main business actually fails. MSME actors must recognize their business, by understanding the strengths, weaknesses, opportunities and threats of their business in order to further increase the stability of their business, so as not to fall into the abyss of failure, so that their business can be sustainable.